THE EFFECTIVENESS OF E-PORTFOLIO ON STUDENTS' WRITING SKILLS AT SMA NEGERI 21 GOWA - Lisa Sari; Ariana; Mallombasi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the effectiveness of using e-portfolio, especially GoogleSites, in improving students writing skills, focusing on two main aspects: grammarand organization. This research was conducted at SMA Negeri 21 Gowa using aquantitative approach with a pre-experiment design. A total of 35 students fromclass XI MIPA 1 were selected as research samples through purposive sampling,considering their relevance and availability for the study. To collect data, studentswere given writing tests before (pre-test) and after (post-test) the application of e-portfolio. The test was designed to evaluate their writing performance in terms ofgrammatical accuracy and organization. The students developed and uploadedtheir writing assignments through Google Sites, which allowed for continuousfeedback and revision throughout the learning process. The data collected wasthen analyzed using Paired Sample T-Test in SPSS to determine if there was astatistically significant difference in students writing performance before and afterthe treatment. The findings showed significant improvement in both aspects ofwriting. The average grammar score increased from 47.14 to 80.71, reflecting anincrease of 71.21%, while the organization score increased from 49.28 to 82.14, oran increase of 71.11%. Statistical analysis showed a significance value of 0.000 (p< 0.05), which confirmed the effectiveness of the e-portfolio. These results suggestthat integrating digital tools such as Google Sites into writing instruction can fosterbetter learning outcomes, increase student engagement, and encourage greaterautonomy in the writing process.